(3SjGSGJ eDSSGJ GdfbO GdOhdjI h GdJYdje (B:s (3OQGSI JMdjdjI (B/s - (3GdYJjbj, EHQGgje eQYjs ((3GdGScfOQjI(B: s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ(B, s, 2006)
(3Cge GdJZjQGJ GdYGdejI GdeYGUQI GdJj JDKQ aj GdfXe hGdSjGSGJ GdJYdjejI,eDSSGJ GdfbO GdOhdjI(B:(3GdJhLgGJ GdYGeI hSjGSI GdJYdje;GdSjGSI GdJYdjejI aj eUQ hCge Gdbhi GdeDKQI ajgG,eDSSGJ GdfbO GdOhdjI hGdSjGSI GdJYdjejI aj eUQ,GdGfYcGSGJ GdeHGTQI dSjGSGJ eDSSGJ GdfbO GdOhdjI Ydi GdJYdje aj eUQ,GdGfYcGSGJ ZjQ GdeHGTQI dSjGSGJ eDSSGJ GdfbO GdOhdjI Ydi GdJYdje aj eUQs
(3HHdjhZQGajG(B:(3U(B.419-459(3;agQS GdLOGhd hGdCTcGd(B:(3U(B.466-467s
Keywords: (3UfOhb GdfbO GdOhdj,JYdjes